Developing Business Strategy of Tribece Urban Market - Tunggadevi, Vincya; Gustomo, Aurik (Journal of Business and Management, 2014)
TriBeCa Urban Retreat is one of a beauty salonÃ‚Â that located in the heart of Bandung. The problem in TriBeCa Urban Retreat is in capturing larger market to increasing sales growth, which is the unpreparedness in capturing larger market while the competitors are increasing agressively. The internal problem in human resource, also may cause declining the standard quality of TriBeCa. The purpose of this research is to develop the business strategy to analyze the company ability to compete and help the business to grow, which supported by the functional strategy in resolving the business internal problem. This research uses PorterÃ¢â‚¬â„¢s generic competitive to determine the most suitable competitive strategies for TriBeCa Urban Retreat.. To support the business strategy, the functional strategy is more focused on marketing strategy and Human Resource (HR) strategy. The primary data for this research was obtained by interviewing the owner of TriBeCa and also some of the customers by using convenience sampling, to define the business focus of TriBeCa, by adapting from SERVQUAL dimension.The result of this analysis, TriBeCa can be the product leader to capture the larger market and increase the sales growth. Based on characteristic of PorterÃ¢â‚¬â„¢s Generic Competitive Strategy, the differentiation focus strategy is the most suitable and feasible for TriBeCa Urban Retreat. Horizontal integration, in opening another branch not necessarily needed because the existing place still capable in handling the expected number of customers.Keywords : TriBeCa Urban Retreat, Salon Industry, Business development, Strategic Development, PorterÃ¢â‚¬â„¢s Generic Competitive Strategy